(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This study object is to analyze the existence of the wage gap and discrimination by gender and color of the southern region of Brazil in the year of 2015. Through database from the National Household Sample Survey (PNAD) of the Brazilian Institute of Geography and Statistics (IBGE), the peculiarities of the employed population were extracted based on variables of the masculine and feminine gender, skin color, age, experience, years of study, monthly salary, urban and rural area. Based on the analysis of total salary differentials and other elements that impact and characterize gender and color differentiation, the Oaxaca-Blinder econometric method was used. There was a considerable difference in the wage gap between men and women, even for women with more years of education and working more hours than men. As for skin color, there is a wage difference for men and women even though they are in the same age group and who present similar years of experience, that is, there is a discriminatory factor regarding color and gender.